2020
DOI: 10.21203/rs.3.rs-36117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Results Following Surgical Resection of Recurrent Chordoma Of the Spine: Experience in a Single Institution

Abstract: Background: Chordoma of the spine is a low-grade malignant tumor with vague and indolentsymptoms thus large tumor mass is encountered at the time of diagnosis in almost cases and makes a difficult for En-bloc free-margin resection. Salvage therapyfor recurrent chordoma is very challenging due to its relentless nature and refractory to adjuvant therapies. The aim of this present study was to report the oncologic outcome following surgical resection of chordoma of the spine.Materials and Methods:Retrospective re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…3,517 These studies demonstrated poor overall local recurrence-free survival and overall survival, but en bloc and gross total excision tend to improve survival rates. 3,4,6,17,18…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3,517 These studies demonstrated poor overall local recurrence-free survival and overall survival, but en bloc and gross total excision tend to improve survival rates. 3,4,6,17,18…”
mentioning
confidence: 99%
“…3,[5][6][7][8][9][10][11][12][13][14][15][16][17] These studies demonstrated poor overall local recurrence-free survival and overall survival, but en bloc and gross total excision tend to improve survival rates. 3,4,6,17,18 Our group previously reported the outcomes of a focused series of primary mobile spine chordomas treated surgically. 19 This study demonstrated the…”
mentioning
confidence: 99%
See 1 more Smart Citation